Logique du sens - Deleuze, Gilles 1925-1995 (Paris Éditions de Minuit, 1969)
An exploration of meaning and meaninglessness or "commonsense" and "nonsense" through metaphysics, epistemology, grammar, and eventually psychoanalysis, The Logic of Sense consists of a series of thirty-four paradoxes followed by an appendix that contains five previously published essays, including a brief overview of Deleuze's ontology entitled "Plato and the Simulacrum".
The book introduces Deleuze's philosophy of the event and of becoming as well as the emergence of the plane of immanence and the body without organs, mythic conceptions of time (Chronos and Aion), the structure of games, and textual analyses of works by Lewis Carroll, Seneca, Pierre Klossowski, Michel Tournier, Antonin Artaud, F. Scott Fitzgerald, Melanie Klein, Friedrich Nietzsche, Stéphane Mallarmé, Malcolm Lowry, Émile Zola and Sigmund Freud.
Includes bibliographical references.
Keywords: Philosophy; Semantics